Surface protective coatings on Mg alloys – A review. (2021) - Chandra, Divya; Ram Chauhan, Nathi
Abstract: The drawbacks of magnesium and its alloys are low wear resistance and highly corrosive nature restrict its use in automobile, aircraft, Electronics as well as in medical field. So to overcome this problem coating is an option by which mechanical and tribological properties of magnesium and its alloys can be enhanced. Coating may be monolayer, multi layer or composite coating. Coating is a surface treatment technique which enhances the surface property of substrate material but keeping the advantageous properties intact throughout its cross section. This review gives the idea to future researchers on the performance of coatings on magnesium alloys, modifying many properties.